Study on the isolation of secondary metabolites and their biological activities of the endophytic fungus Aspergillus fumigatus 06T03 from the soil of Aegiceras corniculatum - DAI Ziteng; WEI Xia; LIU Yanying; YOU Zhengliang; WU Chenghua; WANG Juan; SHEN Zhangyang; XING Shangping; HUANG Qianchan; ZHU Dan (Guangxi Yike Daxue xuebao)
Objective To investigate the isolation and purification of the secondary metabolites and their potential biological activity in the endophytic fungus Aspergillus fumigatus 06T03 from the soil of Aegiceras corniculatum. Methods The strain was fermented on a large scale using rice medium, and then extracted by soaking ethyl acetate and concentrated under reduced pressure to obtain a crude extract of ethyl acetate. A variety of modern chromatographic techniques such as silica gel column chromatography, Sephadex LH-20 gel column chromatography, high -performance liquid chromatography were used to separate the chemical components of the crude extract. Their structures were determined by using comprehensive spectral techniques such as high-resolution mass spectra (MS) and nuclear magnetic resonance (NMR) spectroscopy. The antineoplastic and anti-inflammatory activities of the monomers were evaluated using cell counting kit-8 (CCK-8) assay and Griess assays. Results Nine compounds were isolated from the rice fermentation products of Aspergillus fumigatus 06T03 and identified as Monomethylsulochrin (1), Questin (2), Demethylsulochrin (3), Fumiquinazoline C (4), Fumiquinazoline J (5), Azaspirofurans A (6), Pseurotin A (7), N-[2-(4-hydroxyphenyl) ethenyl]formamide (8), and Pyripyropene A (9). Among them, compounds 1-3 belonged to anthraquinones, and 4-9 belonged to alkaloids. The results showed that compounds 1-9 failed to exhibit obvious antineoplastic activity against Huh7 cells, ovarian carcinoma cells (A2780), and breast cancer cells (MDA-MB-231), while compounds 1, 3, 6, 7, 8, and 9 had certain antiinflammatory activities. Conclusion Nine monomeric compounds, except compound 2 which has been isolated before, have been isolated for the first time from the endophytic fungus Aspergillus fumigatus 06T03 from the soil of Aegiceras corniculatum. Compounds 1, 3, 6, 7, 8, and 9 have certain anti-inflammatory activities. This study enriches the chemical diversity of the secondary metabolites of endophytic fungus from the soil of Aegiceras corniculatum, and provides basic data for subsequent further development.